Hubungan Antara Faktor Individu dan Terjadinya Kelelahan (Fatigue) pada Pekerja Kantor di Masa Transisi Pandemi ke Endemi Covid-19 - Hernayanti, Maghfira; Kurniawidjaja, L. Meily; Sakina, Nova Amalia (National Journal of Occupational Health and Safety, 2022)
The Covid-19 pandemic has changed almost all aspects of human life, including the workforce. The Work from Home (WFH) policy causes irregular working hours. This causes fatigue in workers during the transition from the pandemic to the Covid-19 endemic. Many factors cause work fatigue to occur, one of which is individual factors. This study aims to determine the correlation between individual factors (family social life, sleep quality, sleep quantity, health disorders, psychological, and unhealthy behavior) with the occurrence of fatigue in office workers during the transition from the pandemic to the Covid-19 endemic. Data collection was carried out by disctributing questionnaires via google form to 202 worker respondents in DKI Jakarta. Bivariate statistical analysis with Chi-Square multivariate with multiple logistic regression was used with SPSS v 21 software. The results showed that from the Chi-Square test, sleep quality (p 0.001), health problems (p 0.016), family social life (p 0,012), and unhealthy behavior (p 0.033) has a significant relationship to the incide of fatigue. While the results of the logistic regression test of the prediction model, the variables of sleep quality (p 0,017; OR 2,729), health disorders (p 0,014; OR 2,484) and bad behavior (p 0,010; OR 2,579) have an influence on the incidence of fatigue. The conclusion from this study is that poor sleep quality, health problems and poor bad behavior can affect the incidence of fatigue in workers in DKI Jakarta during the transition from the pandemic to the Covid-19 endemic.